The Effect Of Massage At Point P6 On Reducing The Level Of Emesis Gravidarum In Pregnant Women In The First Trimester At The Landasan Ulin Public Health Center, Banjarbaru - Aura Maharani Utomo; Yenny Oktavitasari; Rizki Amalia; Darmayanti Wulandatika (Journal of Midwifery and Reproduction, 2026)
Emesis gravidarum is a common complaint in the first trimester of pregnancy and can negatively impact maternal well-being and fetal development if not promptly addressed. One non-pharmacological approach that is gaining popularity is acupressure therapy at the P6 point. This study aimed to analyze the effect of massage at the P6 point on reducing emesis gravidarum levels in first-trimester pregnant women at the Landasan Ulin Public Health Center in Banjarbaru. The study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 15 respondents selected using a total sampling technique. The intervention, which involved massage at the P6 point, was performed for three consecutive days, twice daily for two minutes. The level of emesis gravidarum was measured using the Pregnancy-Unique Quantification of Emesis (PUQE) instrument. Data analysis using the Wilcoxon test showed a significant reduction in emesis gravidarum levels, with a mean pretest score of 2.93 and a posttest score of 2.00 (p < 0.001). These findings indicate that massage at the P6 point is effective in reducing nausea and vomiting in pregnant women in the first trimester. P6 massage can be a safe, simple, and self-administered non-invasive and non-pharmacological therapy alternative. This therapy is recommended for implementation in nursing practice and maternal health services in primary healthcare facilities. This research provides a foundation for future researchers to further explore non-pharmacological therapies, specifically P6 point massage, for emesis gravidarum in first-trimester pregnant women. Researchers are encouraged to replicate the study with a larger sample size and explore combinations of these methods with other relaxation techniques and educational videos to enhance effectiveness.